Effects of self-assessment and teacher feedback on undergraduate students’ argumentative writing performance and self-regulated learning - Vasu, Kayatri (2020)
Lack of English writing skills is still an issue among Malaysian undergraduate students despite having learnt English for about 11 years before students enter universities. In universities, different genres of English writing are taught to further develop them to become competent writers. However, till today, students’ poor English writing skills is still one of the biggest concerns in the Malaysian education system due to their lack of active learning. In the current research context, teachers are committed to ensuring that students are aware of their writing proficiency level, and the kind of errors they make in their writing. This explains why direct teacher feedback is the feedback strategy practiced over the years in institutions. However, this form of feedback has caused students to be very dependent on teachers. Self-assessment is a supplementary strategy that ensures students ‘have more control of their learning with sufficient support from the teacher. This study investigated the effects of self-assessment and indirect teacher feedback on argumentative writing performance and self-regulated learning (SRL). A quasi-experimental design with an embedded experimental model was used in this research, as this study collected both quantitative and qualitative data. The quantitative data were obtained through the Self-Regulation Strategy Inventory Self-Report (SRSI-SR) developed by Cleary (2006), and argumentative writing tests. The qualitative data were derived from SRL microanalytic interviews, and learner diary entries. An independent sample t-test and Analysis of Variance were used for the quantitative analysis. For qualitative data, thematic analysis based on the Cyclical Model of Self-Regulated Learning (Zimmerman, 2000) was employed. The results revealed that both indirect teacher feedback, and the use of self assessment checklists improved overall argumentative writing performance. However, self-assessment improved writing performance more than teacher feedback in terms of content, overall effectiveness, and organisation. In terms of SRL behaviour, both self-assessment and teacher feedback helped learners become more self-regulated. Nevertheless, teacher feedback did not reduce maladaptive behaviours in the learners as much as self-assessment. The comparison of the quantitative and qualitative analyses supported the conclusion that self-assessment leads to significant development in self-regulated learning. The conclusions of the study suggest that self-assessment is an effective instructional practice that not only promotes writing performance, but also self regulated learning in terms of goal setting, strategy planning, strategy use, attribution and adaptive inference. It also suggests that self-assessment be the main instructional practice, not just as an alternative, both now and in the future.